The benefits of working together in diabetic foot care for the vulnerable patient. (28th January 2016) - Edmonds, Michael
Abstract: The patient with a diabetic foot is extremely complex and vulnerable to tissue necrosis because three great pathologies come together in the diabetic foot: neuropathy, ischaemia and infection. As a result of neuropathy, the signs and symptoms of external physical insults and of infection may be minimal. Nevertheless, the pathology emanating from such insults and infection proceeds rapidly without the body being aware of them and the end‐stage of tissue death is quickly reached. Thus, the window of opportunity for intervention is limited and is often missed. From a practical point of view, the diabetic foot can be divided into two main entities: the neuropathic foot and the ischaemic foot. The neuropathic foot is vulnerable to attack from mechanical forces leading to ulceration and also to bacteriological invasion resulting in tissue necrosis. The diabetic ischaemic foot commonly presents as the neuroischaemic foot which is characterised by both ischaemia and neuropathy leading to ulcers commonly seen on the margins of the foot and toes. These ulcers are also prone to bacteriological invasion, again resulting in tissue necrosis. However, it has been shown that such a vulnerability of the diabetic foot patient to tissue necrosis can be successfully managed by the development of a multidisciplinary diabetic foot team which provides prompt outpatient care in a diabetic foot clinic and inpatient care on the hospital wards. Such a development has promoted advances in clinical care, research and education, has stimulated the creation of the subspecialty of diabetic foot care, and has shown that most major amputations can be avoided. Copyright © 2016 John Wiley & Sons.